Toxocariasis in children attending a Public Health Service Pneumology Unit in Paraná State, Brazil - Guilherme, Edson V.; Marchioro, Ariella A.; Araujo, Silvana M.; Falavigna, Dina Lúcia Morais; Adami, Carolina; Falavigna-Guilherme, Gustavo; Rubinsky-Elefant, Guita; Falavigna-Guilherme, Ana Lucia (Revista do Instituto de Medicina Tropical de São Paulo, 2013)
The enzyme-linked immunosorbent assay (ELISA) is the most widely used tool to detect anti-Toxocara IgG antibodies for both serodiagnostic and seroepidemiological surveys on human toxocariasis. In the last eight years a high prevalence of toxocariasis (32.2-56.0%) has been reported in children attending public health units from municipalities in the state of Paraná, Brazil. Therefore, the aim of this work was to compare the frequency found among the general child population with that of children attending a public pneumology service in Maringá, Paraná, Brazil and describe the laboratorial, clinical and epidemiological findings. The research was conducted at the Consórcio Público Intermunicipal de Saúde do Setentrião Paranaense (CISAMUSEP) from July 2009 to July 2010 among children aged between one and 15 years. From a total of 167 children studied, only 4.2% (7/167) tested positive for anti-Toxocara spp. IgG antibodies and presented mild eosinophilia (2/7), increased serum IgE levels (6/7) and a positive allergy test for mites (5/7). The presence of pets (dogs or cats) at home did not correlate with the seroprevalence. In conclusion, cases of toxocariasis involving the respiratory tract are rare in children attending a public health pneumology unit in the northwestern region of Paraná State, despite the high prevalence of this type of toxocariasis among the infantile population attending Basic Health Units in the same geographical area.